Fertility Decline: And Falling School Enrolment - J. Retnakumar and P. Arokiasamy (Economic and Political Weekly, Vol. 38, No. 46 (Nov. 15-21, 2003), pp. 4827-4830, 2003)
An enquiry into the impact of declining fertility on school infrastructure facilities in the lower primary schools in a district with one of the lowest population growths in the country finds that despite a rapid decline in enrolment there is no real surplus of such facilities. Instead, there has been an improvement in the quality of the infrastructure